2021
DOI: 10.3389/fcell.2021.580754
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-coding RNA ENST00000453774.1 Confers an Inhibitory Effect on Renal Fibrosis by Inhibiting miR-324-3p to Promote NRG1 Expression

Abstract: Progressive or chronic renal diseases arise from a process of destructive renal fibrosis. Therefore, the molecular basis of renal fibrosis has attracted increasing attention. In this investigation, we set out to elucidate the potential interaction among long non-coding RNA ENST00000453774.1 (lncRNA 74.1), microRNA-324-3p (miR-324-3p), and NRG1, and to investigate their roles in the context of cellular autophagy and renal fibrosis. We collected 30 renal fibrosis tissue samples for analysis. In other studies, HK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…This type of interaction not only regulates the proliferation and survival of cells, but also influences the immune microenvironment, particularly the infiltration and function of M2 macrophages and neutrophils [ 50 ]. By studying in vitro cell line models, it has been discovered that the downregulation of NRG1 or the use of PI3K/AKT inhibitors can effectively impede cell proliferation and migration, while inducing apoptosis [ 51 ]. In contrast, the utilization of PI3K/AKT signaling agonists enhances the proliferative and migratory abilities of cells, while decreasing the rate of apoptosis [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of interaction not only regulates the proliferation and survival of cells, but also influences the immune microenvironment, particularly the infiltration and function of M2 macrophages and neutrophils [ 50 ]. By studying in vitro cell line models, it has been discovered that the downregulation of NRG1 or the use of PI3K/AKT inhibitors can effectively impede cell proliferation and migration, while inducing apoptosis [ 51 ]. In contrast, the utilization of PI3K/AKT signaling agonists enhances the proliferative and migratory abilities of cells, while decreasing the rate of apoptosis [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study unequivocally demonstrates the significant role of NRG1 in this process. Knocking down NRG1 or using PI3K/AKT inhibitors resulted in a decrease in tumor count and an increase in overall survival in PDX mouse models [ 51 ]. Specifically, the proliferative capacity of cells decreases, the rate of apoptosis increases, while the number of M2 macrophages decreases, and the number of neutrophils increases [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, increasing evidence has demonstrated that energy metabolism plays a major regulatory role in the progression of RF ( Lan et al, 2016 ; Liu et al, 2017 ). Autophagy dysfunction is implicated in the pathogenesis of acute kidney injury and RF diseases ( Nam et al, 2019 ; Yang et al, 2020b ; Tang et al, 2021 ). Existing research further indicates that in RF, the process of autophagy may either promote it by contributing to tubular atrophy and decomposition or prevent it by improving intracellular degradation of excessive type I collagen mediated by TGF-β1 ( He et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…( Yan et al, 2022 ) Besides MIR17HG also inhibits non-small cell lung cancer via functioning as a ceRNA of miR-142-3p. ( Wei et al, 2020 ) Through this regulatory mode, lncRNAs are widely involved in the course of various diseases, including thyroid cancer ( Guo et al, 2021 ), renal fibrosis ( Tang et al, 2021 ), atherosclerotic plaques ( Ann et al, 2021 ), among others.…”
Section: Function Of Lncrnasmentioning
confidence: 99%